2012
DOI: 10.1002/cssc.201200022
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Nitrogen‐Doped Hydrothermal Carbons Derived from Microalgae

Abstract: Nitrogen‐doped carbon materials are synthesized via an effective, sustainable, and green one‐step route based on the hydrothermal carbonization of microalgae with high nitrogen content (ca. 11 wt %). The addition of the monosaccharide glucose to the reaction mixture is found to be advantageous, enhancing the fixation of nitrogen in the synthesized carbons, resulting in materials possessing nitrogen content in excess of 7 wt %, and leading to promising reaction yields. Increasing the amount of glucose leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(86 citation statements)
references
References 30 publications
3
83
0
Order By: Relevance
“…Scheme shows a scheme for the synthesis of CNHPC from enteromorpha. The washed and dried enteromorpha was first mixed with glucose solution for 18 h. The glucose was added to improve the yield and aid N‐doping of carbon . After that the mixed solution was hydrothermally carbonized at 180 °C for 24 h, followed by activation with KOH (KOH/carbon=4:1, by weight) at different temperatures (700 and 800 °C) for 1 h under N 2 atmosphere to obtain CNHPC.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Scheme shows a scheme for the synthesis of CNHPC from enteromorpha. The washed and dried enteromorpha was first mixed with glucose solution for 18 h. The glucose was added to improve the yield and aid N‐doping of carbon . After that the mixed solution was hydrothermally carbonized at 180 °C for 24 h, followed by activation with KOH (KOH/carbon=4:1, by weight) at different temperatures (700 and 800 °C) for 1 h under N 2 atmosphere to obtain CNHPC.…”
Section: Resultsmentioning
confidence: 58%
“…The washed and dried enteromorphaw as first mixed with glucose solution for 18 h. The glucosew as added to improve the yield and aid N-doping of carbon. [22] After that the mixed solution was hydrothermally carbonized at 180 8C for 24 h, followed by activation with KOH (KOH/carbon = 4:1, by weight) at different temperatures (700 and 800 8C) for 1h under N 2 atmosphere to obtain CNHPC. Direct cabonizationo f enteromorphai ni nN 2 was found to give al ow yield of carbon and low content of nitrogen doping.…”
Section: Resultsmentioning
confidence: 99%
“…Carbonization temperature is dependent on the type of starting materials and its decomposition temperature; a range of 150 to 350°C is typically employed [2,[10][11][12][13][14][15]. Hydrothermal carbonization results in efficient hydrolysis and dehydration of biomass and bestows the hydrochar with high OFG (oxygenated functional groups) content which makes it an effective precursor for the production of chemically activated carbon [8,16].…”
Section: Introductionmentioning
confidence: 99%
“…reported carbons from cyanobacteria pyrolysis with surface area of 2184 m 2 /g, showing a specific capacitance of 222 F/g at 5 A/g in 6 M KOH. Several studies reported the hydrothermal synthesis of microalgae‐derived N‐doped carbons,,,,, exhibiting remarkable electrochemical storage performance, attributed to both their high porosity and to the N‐species inherent from the high protein fraction present in microalgae. Macroalgae, an important member of the marine biomass, has also been reported to possess interesting energy storage properties.…”
Section: Introductionmentioning
confidence: 99%